ANALISIS PENERAPAN MANAJEMEN RISIKO PADA PERUSAHAAN PEMBIAYAAN SYARIAH - Silviana Dewi; Arinda Deviana; Almira Nur Laili; Rinda Asytuti (Institut Agama Islam Negeri (IAIN) Ternate, 2022)
The business world recognizes that leasing can be used as an alternative financing, especially in the delivery of capital goods or other equipment. Finance or leasing companies are the priority chosen by the community as credit to obtain assets. Today, Islamic and conventional finance companies pay less attention to the principle of prudence in dealing with financing risks. With easy terms for making credit flows, finance companies face the risk of bad debts. This research method uses a library research approach that comes from credible journals and authoritative news stories. In this method the author tries to give a real picture of the financing risks that occur. The results of the study indicate that financing is a gift in the form of money which is carried out on the basis of mutual agreement by both parties between the owner of capital and the recipient of capital on the condition that the return of financing is carried out periodically within the time specified in accordance with the agreement. Financing risk management is risk management that focuses on risks that can be managed using financial instruments. Keywords: Management; Risk; Financing